Out of the Dark - Book 1 - Weber, David, 1952- (New York : Tor, 2010)
A master sergeant prowling the back country of the Balkans and a firearms instructor and former Marine find themselves at the center of a growing network of resistance against an invading force of alien, carnivorous Shongari intent on annihilating the human race.
"A Tom Doherty Associates book."
Keywords: Extraterrestrial beings -- Fiction; Space warfare -- Fiction; Vampires -- Fiction; Science fiction; War stories